Investigation of the switched inductor circuit for harmonics compensation - Argyrou, Maria C.; Marouchos, Christos; Darwish, Mohammed K.; Iosif, Eftihia; Paterakis, Fotis (My University, 2017)
The switched inductor is a new circuit configuration for electronically varying the effective inductance of an inductor. In conjunction with a capacitor, filters with electronically adjustable tuning frequency can be constructed. This filter has the advantage to follow specific harmonics at the output of an inverter with varying frequency. In this way selective harmonic elimination is possible.
Keywords: Active filters; Harmonic current elimination; Switched capacitors